Smart Personal Safety Device Using IoT - Adwaith Shaji; Gayathri V.S.; Mithra M. Lal; Ashida Pradeep (International Journal of Machine Systems and Manufacturing Technology, 2024)
Our goal is to identify a considering the rapid advancement of science and technology and our heavy dependence on technological features, a solution to this important problem for women. We are focusing to make a smart personal safety device that helps women’s and all peoples who need help or an extra security. This project not only helps women’s but also helps children, old age people and disabled people. The design supports a smart location and tracking system and alert notification, GPS, GSM, Audio video recording facility, and a face-recognition image capture system and to minimize the weight of the model. We implemented Li-Ion battery. The high-quality camera and voice recorder cooperate with GSM system and send the visuals and recordings to nearest police station or relatives. It not only sending it stores the visual and recording in cloud storage for legal purposes. The suggested model also includes an electric shock with a wireless system activator and a siren. The design features have been carefully considered and confirmed to provide women with the best safety tool available.
Keywords: GPS; GSM; IOT; Li-ion battery; Smart bag; Video recording; Woman Safety